2018
DOI: 10.7146/lom.v10i18.96143
|View full text |Cite
|
Sign up to set email alerts
|

From professors’ barriers to organisational conditions in ICT integration in higher education

Abstract: The responsibility of innovation with ICT in education has mainly been placed on professors as pivotal to adoption. However, professors are part of complex organisations with inherent obstacles related to their cultural and historical conditions. Despite some studies have stablished the complexity of internal and external barriers separately, others highlight on the importance of considering teachers' beliefs and contextual factors together. In this regard, the article aims to explore the underlying organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The study evidences that the integration of technology for teaching and learning purposes is not an individual activity. Even though some researches focus on the individual level of professors' attitudes towards technology (Salleh, 2016), other highlight the importance of not only helping overcome professors barriers but also enabling organizational conditions (Castro & Nyvang, 2018).…”
Section: Discussion On Challenges Of Tpd-ict a Collective And Cross-level Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The study evidences that the integration of technology for teaching and learning purposes is not an individual activity. Even though some researches focus on the individual level of professors' attitudes towards technology (Salleh, 2016), other highlight the importance of not only helping overcome professors barriers but also enabling organizational conditions (Castro & Nyvang, 2018).…”
Section: Discussion On Challenges Of Tpd-ict a Collective And Cross-level Developmentmentioning
confidence: 99%
“…As stated by Kennedy (2005), transformative models of TPD increase the capacity for professional autonomy. Due to the complex dynamics of barriers in professors when it comes to the adoption of ICT (Castro, 2016), and the importance of institutional conditions (Castro & Nyvang, 2018), TPD faces challenges for a successful use of technology in education. According to Kennedy (2005), transformative models are not without tensions.…”
Section: Introductionmentioning
confidence: 99%
“…A barrier can be defined as anything that prevents a specific objective from occurring. Within the area of technology adoption, studies have demonstrated that college lecturers appreciate the importance of technology adoption and how it is valuable to students' motivation while promoting students' engagement (Castro & Nyvang, 2018;Ottenbreit-Leftwich et al, 2010). Even though this may be so, college lecturers are experiencing considerable difficulties in the integration process due to barriers (Ertmer et al, 1999).…”
Section: Barriers To Technology Adoptionmentioning
confidence: 99%
“…Even though this may be so, college lecturers are experiencing considerable difficulties in the integration process due to barriers (Ertmer et al, 1999). For these reasons, researchers have been driven to gain an in-depth understanding of `the various factors that contribute to technology adoption (Castro, 2016;Castro & Nyvang, 2018). Some of the most common barriers are lecturer-related variables that include the self-confidence of college lecturers and the lecturer's belief in the usefulness of the technology (Hur et al, 2016;Tondeur et al, 2016).…”
Section: Barriers To Technology Adoptionmentioning
confidence: 99%
See 1 more Smart Citation